2011
DOI: 10.3171/2011.6.jns101989
|View full text |Cite
|
Sign up to set email alerts
|

Hospital costs, incidence, and inhospital mortality rates of traumatic subdural hematoma in the United States

Abstract: Nationally, frequency and cost of traumatic SDH cases are increasing rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…This is similar to the 15% operatively treated traumatic SDH mortality rate, but substantially higher than the 7% operatively treated nontraumatic SDH mortality rate from NIS data. 4,10 The most likely explanation for this more than 2-fold difference is that NIS only captures inpatient mortality, whereas NSQIP captures all deaths within 30 days, including at home, in rehabilitation facilities, and in hospices. 1 In addition, the distinction between a traumatic and a nontraumatic SDH based on ICD-9 coding appears dubious, as truly nontraumatic SDH is a rare condition.…”
Section: Mortality Ratementioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to the 15% operatively treated traumatic SDH mortality rate, but substantially higher than the 7% operatively treated nontraumatic SDH mortality rate from NIS data. 4,10 The most likely explanation for this more than 2-fold difference is that NIS only captures inpatient mortality, whereas NSQIP captures all deaths within 30 days, including at home, in rehabilitation facilities, and in hospices. 1 In addition, the distinction between a traumatic and a nontraumatic SDH based on ICD-9 coding appears dubious, as truly nontraumatic SDH is a rare condition.…”
Section: Mortality Ratementioning
confidence: 99%
“…4,10 However, nontraumatic SDH in this context does not represent true spontaneous hemorrhage, but rather an SDH without a documented known injury. Hence, despite the difference in coding, these patients were considered together in this study.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Nevertheless, Bartels et al reported that a large majority (69%) of cases of ISH included in their review required operative intervention (e.g., craniotomy, burr holes), 6 contrary to other forms of subdural hematoma. 19 The clinical manifestations of ISH depend on the specific location and size of the hematoma and the progression of the neurological symptoms that it produces. 13 In our patient, the clinical picture was assumed to be PDPH because of the temporal relationship between the appearance of the patient's symptoms and the onset of a positiondependent headache after accidental dural puncture.…”
Section: Discussionmentioning
confidence: 99%
“…62 A 2011 study on mortality associated with traumatic SDH indicated a mortality rate of between 10% and 20%. 63 While clearly the decline in mortality cannot be attributed to improved imaging alone, it certainly plays a role. Within a few years of the introduction of CT, pneumoencephalography was extinct and the use of angiography decreased.…”
mentioning
confidence: 99%